Digital CRM Adoption in Creative MSMEs The Role of Customer Relationship Capability in Increasing Competitive Advantage - Wiwin Riski Windarsari (PT Maju Malaqbi Makkarana, 2026)
This study investigates the role of Digital Customer Relationship Management (CRM) adoption in enhancing competitive advantage among creative small and medium-sized enterprises (SMEs), with a particular focus on the mediating role of customer relationship capability (CRC). Grounded in the Resource-Based View and Dynamic Capabilities, this research proposes that digital CRM functions as a strategic resource whose value is realized through organizational capabilities. A quantitative approach was employed using survey data collected from 200 creative SMEs. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that digital CRM adoption has a significant positive effect on customer relationship capability and competitive advantage. Furthermore, customer relationship capability significantly influences competitive advantage and partially mediates the relationship between digital CRM adoption and competitive advantage. These findings demonstrate that the impact of digital CRM on competitive advantage is not direct but largely depends on the firm’s ability to transform technological resources into relational capabilities. This study contributes to the CRM literature by addressing the “black box” between technology adoption and firm performance through a capability-based perspective. It also integrates resource-based and dynamic capability views in explaining how SMEs leverage digital technologies to achieve sustainable competitive advantage. Practically, the study suggests that SMEs should not only invest in digital CRM systems but also develop internal capabilities to effectively manage customer relationships. The findings provide strategic insights for SMEs seeking to maximize the benefits of digital transformation in increasingly competitive markets.